FLOUTING AND IMPLEMENTING MAXIMS IN SARAH SECHAN TALK SHOW - Lastri Wahyuni Manurung (Kantor Bahasa Kepulauan Riau, 2020)
In performing utterances, some people do not always want to cooperate because they have certain reasons such as to avoid unpleasant situations, to be polite, and to make jokes. This research was conducted to find out the most dominant flouting and fulfillment of maxim in some speech acts. The theory of cooperative principles and the speech act were used to find out problems. The data were taken from Sarah Sechan talk show. The most flouting maxim was the quantity and manner and the fulfillment of the quality maxim in the assertive-to-tell speech acts.